MEASUREMENT OF SPATIAL DISTRIBUTION OF MECHANICAL STRESSES IN ULTRASONIC WAVEGUIDE SYSTEMS BY MEANS OF SENSORS BASED ON VILLARI EFFECT - D. A. Stepanenko; K. A. Bogdanchuk; V. T. Minchenya (Приборы и методы измерений)
Problems of design, fabrication and application of sensors for measurement of mechanical stresses in ultrasonic waveguide systems based on Villari effect and providing spatial resolution of measurements are considered. Results of experimental studies of spatial distribution of vibration parameters in waveguide systems for ultrasonic thrombolysis are presented. Technique of calibration and potential applications of the sensors are described.